The use of psilocybin in the treatment of psychiatric disorders - review - Justyna Woźniak; Rafał Bogacz; Magdalena Gaik; Ewa Uram; Inga Magda; Karol Womperski; Magdalena Osuch (Kazimierz Wielki University, 2023)
Introduction: The word "psychedelic" derives from the Greek language and can be loosely translated as "mind manifesting" which is to convey that these substances allow the mind to unleash its hidden potential. Psilocybin is considered to be a "classic psychedelic" and is most commonly found in the form of so-called "magic mushrooms". Due to its unique properties psilocybin has been used during religious ceremonies and rituals for centuries and more recently also explored in a medical context. Nowadays many studies are being carried out to prove the efficacy of its use in the treatment of various psychiatric disorders.  Aim of study: Review of the current knowledge on the subject of psilocybin applied in the treatment of psychiatric disorders, such as major depressive disorder, treatment-resistant depression and addiction. Methods and materials: A review of chosen literature was carried out in the PubMed database and Google Scholar using the following phrases: psilocybin, psychedelics, psychedelic-assisted therapy, major depressive disorder, addiction. Results: Recent studies suggest that psilocybin may be an effective form of treatment for cancer-related psychiatric distress, treatment-resistant depression and addiction. There are some reports of psilocybin being useful when treating obsessive-compulsive disorder and cluster headaches. Conclusions: More large-scale, randomized, placebo-controlled studies are required to prove these promising findings. Psychological support is crucial during the treatment with psilocybin.